Observations on small tunas caught in the tuna trap fishery off southern Portugal (NE Atlantic) between 1996 and 2014 - Lino, Pedro (2020)
This study reports on the trends of small tuna catches from a tuna trap operating off the southern coast of Portugal between 1996 and 2014. Landing and catch at size data from one tuna trap were available for bullet tuna (Auxis rochei), Atlantic bonito (Sarda sarda) and little tunny (Euthynnus alletteratus). Trends of intra- and inter-annual catches for the three species were analyzed. Landings occurred mostly during the 2nd and 3rd quarters, with peaks in May for A. rochei and in September for S. sarda and E. alletteratus. Catch at size data shows that similar size ranges of the three species were captured.